Kaya's hero : a story of giving - Shaw, Janet Beeler, 1937- (Pleasant Company, 2002)
In 1764, Kaya greatly admires a courageous and kind young woman in her Nez Perce village and wants to be worthy of her respect. Includes historical notes on the winter activities of the Nez Perce Indians, including ceremonies and crafts.